Identification of a TIGIT-expressing CD8+ T cell subset as a potential prognostic biomarker in colorectal cancer - Cao, Shouli; Wang, Meidan; Sun, Weiqiang; Ma, Zhibin; Yang, Kun; Li, Ting; Zhu, Xuedan; Pei, Yang; Pan, Mingyue; Wang, Liqun; Ding, Honglin (Frontiers in Immunology, 2025)
TIGIT is an inhibitory immune checkpoint receptor on T cells and NK cells that mediates immunosuppressive effects by binding to ligands on malignant or antigen-presenting cells. In colorectal cancer (CRC), immune checkpoint inhibitors like anti-PD-1 show therapeutic promise, but many patients experience resistance or relapse. Therefore, identifying robust immune biomarkers for predicting disease progression and therapeutic response is critical. Analysis of transcriptomic data from CRC patients revealed that high TIGIT expression is associated with poorer overall and disease-free survival. TIGIT expression also correlated with immune infiltration, particularly CD8+ T cells. Single-cell RNA sequencing identified a distinct subset of TIGIT+PD-1+CXCL13+ CD8+ T cells enriched in CRC patients. In vitro co-culture experiments confirmed that this phenotype is induced by tumor cells, suggesting a tumor-driven mechanism of T cell dysfunction. This TIGIT+PD-1+CXCL13+ CD8+ T cell population may serve as a potential biomarker for prognosis and immunotherapy response in CRC.